The Iranian Vital Horoscope; Appropriate Tool to Collect Health Statistics in Rural Areas - A Khosravi; ME Motlagh; SH Emami Razavi (Tehran University of Medical Sciences, 2009)
"nThis paper aims to describe the Iranian Vital Horoscope System. This system has been designed to collect and display vital events within the community. Baseline population data are collected by health workers (Behvarz), and are entered onto the Vital Horoscope Chart. The objective of this data collection system is to compile relevant data to quantitatively assess the performance of the health unites at the different levels each year, according to conventional health indicators. Assessing indices reported based on this data sources confirmed the consistency of the Vital Horoscope as a data collection mechanism and provided face validity of the data source. However, further study is needed to evaluate content validity and reliability of data from this system.